Development of a Methodology of Evaluation of Financial Stability of Commercial Banks - Brauers, Willem Karel M.; Ginevičius, Romualdas; Podviezko, Askoldas (Panoeconomicus, 2014)
The field of evaluation of financial stability of commercial banks, which emanates from persistent existence of financial crisis, induces interest of researchers for over a century. The span of prevailing methodologies stretches from over-simplified risk-return approaches to ones comprising large number of economic variables on the micro- and/or macro-economic level. Methodologies of rating agencies and current methodologies reviewed and applied by the ECB are not intended for reducing information asymmetry in the market of commercial banks. In the paper it is shown that the Lithuanian financial system is bank-based with deposits of households being its primary sources, and its stability is primarily depending on behavior of depositors. A methodology of evaluation of commercial banks with features of decreasing information asymmetry in the market of commercial banks is being developed by comparing different MCDA methods. Key words: MOORA, MULTIMOORA, Bank evaluation, Financial stability, CAMEL. JEL: C44, C61, G21, O22.